The Parkinson's disease-associated protein DJ-1 plays a positive nonmitochondrial role in endocytosis in Dictyostelium cells - Suwei Chen; Sarah J. Annesley; Rasha A. F. Jasim; Vanessa J. Musco; Oana Sanislav; Paul R. Fisher (The Company of Biologists, 2017)
The loss of function of DJ-1 caused by mutations in DJ1 causes a form of familial Parkinson's disease (PD). However, the role of DJ-1 in healthy and in PD cells is poorly understood. Even its subcellular localization in mammalian cells is uncertain, with both cytosolic and mitochondrial locations having been reported. We show here that DJ-1 is normally located in the cytoplasm in healthy Dictyostelium discoideum cells. With its unique life cycle, straightforward genotype-phenotype relationships, experimental accessibility and genetic tractability, D. discoideum offers an attractive model to investigate the roles of PD-associated genes. Furthermore, the study of mitochondrial biology, mitochondrial genome transcription and AMP-activated protein kinase-mediated cytopathologies in mitochondrial dysfunction have been well developed in this organism. Unlike mammalian systems, Dictyostelium mitochondrial dysfunction causes a reproducible and readily assayed array of aberrant phenotypes: defective phototaxis, impaired growth, normal rates of endocytosis and characteristic defects in multicellular morphogenesis. This makes it possible to study whether the underlying cytopathological mechanisms of familial PD involve mitochondrial dysfunction. DJ-1 has a single homologue in the Dictyostelium genome. By regulating the expression level of DJ-1 in D. discoideum, we show here that in unstressed cells, DJ-1 is required for normal rates of endocytic nutrient uptake (phagocytosis and, to a lesser extent, pinocytosis) and thus growth. Reduced expression of DJ-1 had no effect on phototaxis in the multicellular migratory 'slug' stage of the life cycle, but resulted in thickened stalks in the final fruiting bodies. This pattern of phenotypes is distinct from that observed in Dictyostelium to result from mitochondrial dyfunction. Direct measurement of mitochondrial respiratory function in intact cells revealed that DJ-1 knockdown stimulates whereas DJ-1 overexpression inhibits mitochondrial activity. Together, our results suggest positive roles for DJ-1 in endocytic pathways and loss-of-function cytopathologies that are not associated with impaired mitochondrial function.